Natural and Designed Cyclic Peptides as Potential Antiviral Drugs to Combat Future Coronavirus Outbreaks - Hilarie Uwamahoro; Willard E. Collier; Toufic O. Nashar; Jesse M. Jaynes; Desmond G. Mortley; Cheryl G. Davis; Getrude G. Kanyairita; Eslam F. Abdelazim; Jean Francois Regis Igiramaboko; Concorde Habineza; Devotha Tumushimiyimana; Umuraza Noella Rutayisire; et al. (Molecules)
The COVID-19 pandemic has underscored the need for effective and affordable antiviral drugs. Anthropogenic activities have increased interactions among humans, animals, and wildlife, contributing to the emergence of new and re-emerging viral diseases. RNA viruses pose significant challenges due to their rapid mutation rates, high transmissibility, and ability to adapt to host immune responses and antiviral treatments. The World Health Organization has identified several diseases (COVID-19, Ebola, Marburg, Zika, and others), all caused by RNA viruses, designated as being of priority concern as potential causes of future pandemics. Despite advances in antiviral treatments, many viruses lack specific therapeutic options, and more importantly, there is a paucity of broad-spectrum antiviral drugs. Additionally, the high costs of current treatments such as Remdesivir and Paxlovid highlight the need for more affordable antiviral drugs. Cyclic peptides from natural sources or designed through molecular modeling have shown promise as antiviral drugs with stability, low toxicity, high target specificity, and low antiviral resistance properties. This review emphasizes the urgent need to develop specific and broad-spectrum antiviral drugs and highlights cyclic peptides as a sustainable solution to combat future pandemics. Further research into these compounds could provide a new weapon to combat RNA viruses and address the gaps in current antiviral drug development.